A N7-guanine RNA cap methyltransferase signature-sequence as a genetic marker of large genome, non-mammalian Tobaniviridae - Ferron, François (2019)
The order Nidovirales is a diverse group of (+) RNA viruses, classified together based on their common genome organisation and conserved replicative enzymes, despite drastic differences in size and complexity. One such difference pertains to the mechanisms and enzymes responsible for generation of the proposed viral 5 RNA cap. Within the Coronaviridae family, two separate methytransferases (MTase), nsp14 and nsp16, perform the RNA-cap N7-guanine and 2 -OH methylation respectively for generation of the proposed m7GpppNm type I cap structure. For the majority of other families within the Nidovirales order, the presence, structure and key enzymes involved in 5 capping are far less clear. These viruses either lack completely an RNA MTase signature sequence, or lack an N7-guanine methyltransferase signature sequence, obscuring our understanding about how RNA-caps are N7-methylated for these families. Here, we report the discovery of a putative Rossmann fold RNA methyltransferase in 10 Tobaniviridae members in Orf1a, an unusual genome locus for this gene. Multiple sequence alignments and structural analyses lead us to propose this novel gene as a typical RNA-cap N7-guanine MTase with substrate specificity and active-site organization similar to the canonical eukaryotic RNA-cap N7-guanine MTase.